Meningkatkan Hasil Belajar Siswa Menggunakan Model Problem Based Instruction Di MTs. Hasanuddin semboro Jember - Winda Riyanto; SIti Roudlatul Hikamah; Umi Nurjanah (FKIP Universitas Islam Jember, 2017)
The Application of the problem-based instruction (pbi) type of learning model to improve student learning outcomes on the interaction of living things with the environment in MTs. Hasanuddin Semboro Jember. This study aims to determine the completeness of student learning outcomes. The type of research used is Classroom Action Research. Based on the results of the study, the average value of student learning outcomes in the first cycle was 73.2 with a percentage of 72%, and in the second cycle it was obtained an average of 82.3 with a percentage of 92%. Student learning outcomes have increased by 20%. This proves that the application of the Problem Based Instruction (PBI) type of learning model can improve student learning outcomes. Keywords: Problem Based Instruction (PBI), learning outcomes.